KAJIAN SOSIOLOGI SASTRA DAN PENDIDIKAN KARAKTER DALAM NOVEL SIMPLE MIRACLES KARYA AYU UTAMI SERTA RELEVANSINYA PADA PEMBELAJARAN SASTRA DI SMA - Teguh Alif Nurhuda; Herman J. Waluyo; Suyitno Suyitno (Jurnal Ilmiah Didaktika, 2017)
This study aims to describe the content of Ayu Utami's Simple Miracles novel in terms of literary sociology and character education. Besides this research also see its relevance to the learning of literature in high school grade 12. This research uses qualitative descriptive method with the subject of Simple Miracles novel. Ayu Utami's novel tells about the life of one family and about the deaths of several family members. The results of this study indicate a social relationship between the characters both in one family member and outside family members. In addition, the results of this study can be deduced from 18 things that are characterized by the characters in this novel, religious, honest, tolerant, independent, democratic, curiosity, friendly, reading, social, and responsibility. This novel also has local cultural features known, religious, and social so that it can be a teaching material in high school grade 12 in accordance with KD 4.1.